Koncepcja opisu konotacji nazw własnych w „Słowniku metafor i konotacji nazw własnych” - Rutkowski, Mariusz (Wydawnictwo „Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The article discusses issues related to the rules for a description and explanation of connotations of proper names in Słownik metafor i konotacji nazw własnych [Dictionary of Proper Names and their Metaphors and Connotations] due to be published soon. The discussion covers a range of detailed problem issues that, in view of the fact that no lexicographical patterns are available, have to be resolved arbitrarily − in particular with reference to the shape or form of definitions in the dictionary.
Keywords: proper names; defining; dictionaries; onomastic lexicography; connotations